Clinical approach to persistent lymphadenopathy in tuberculous lymphadenitis: a narrative review and proposed framework - Praveen Kumar Dubey; Vinay Venugopal; Ranganath Ganga; Dibakar Sahu; Bhoomika Kaushik; Ajoy Behera (The Egyptian Journal of Bronchology, 2026)
Abstract Persistent or enlarging lymphadenopathy during treatment for tuberculous lymphadenitis is common but is frequently misinterpreted as microbiological treatment failure. Residual fibrosis, paradoxical inflammatory reactions, inadequate dosing or adherence, drug resistance, altered drug exposure, and alternative diagnoses may produce similar clinical presentations, while validated response criteria for lymph-node tuberculosis remain lacking. This structured narrative review synthesizes available guidance, observational studies, diagnostic evidence, pharmacokinetic literature, and expert clinical judgement to propose a practical framework for reassessment. The framework emphasizes confirmation of the original diagnosis, correct weight-based dosing, adherence and treatment continuity, recognition of paradoxical reactions, selective use of imaging, individualized repeat tissue sampling, molecular and drug-resistance testing, and consideration of alternative diagnoses. Imaging may define disease extent and complications but cannot reliably distinguish viable bacilli from paradoxical inflammation, sterile necrosis, or residual fibrosis. Repeat sampling may be considered when progressive or discordant disease is present and when the result is likely to alter management. Therapeutic drug monitoring is not routine standard care for drug-susceptible tuberculous lymphadenitis. Evidence supporting its use is very limited, predominantly indirect, and derived mainly from pulmonary or heterogeneous tuberculosis populations. It may be considered only as an optional specialist investigation in exceptional patients after more common causes of apparent non-response have been evaluated. The proposed framework is a practice-oriented and hypothesis-generating synthesis rather than a validated clinical algorithm or evidence-graded guideline. Its components should be individualized according to the clinical context and available resources, and prospective studies are required to validate their diagnostic and therapeutic utility.